Colovesicular fistula from Candida dubliniensis in an immunocompetent resulting in poor outcome - Christine Rizkalla; Jillian Ottombrino; Fahad Malik (Journal of Community Hospital Internal Medicine Perspectives, 2020)
Candida dubliniensis is a rare fungal opportunistic infection originally isolated from the oral cavity of severely immunocompromised individuals. We present a case of a candidiasis infection in a patient with only decompensated liver cirrhosis and diabetes mellitus as his immunocompromising risk factors, resulting in severe fungemia and death within 5 days despite being on antifungal therapy.